Attenuating apoptosis in Chinese hamster ovary cells for improved biopharmaceutical production. Issue 4 (23rd January 2020) - Henry, Matthew N.; MacDonald, Michael A.; Orellana, Camila A.; Gray, Peter P.; Gillard, Marianne; Baker, Kym; Nielsen, Lars K.; Marcellin, Esteban; Mahler, Stephen; Martínez, Verónica S.
Abstract: Chinese hamster ovary (CHO) cells are the predominant host cell line for the production of biopharmaceuticals, a growing industry currently worth more than $188 billion USD in global sales. CHO cells undergo programmed cell death (apoptosis) following different stresses encountered in cell culture, such as substrate limitation, accumulation of toxic by‐products, and mechanical shear, hindering production. Genetic engineering strategies to reduce apoptosis in CHO cells have been investigated with mixed results. In this review, a contemporary understanding of the real complexity of apoptotic mechanisms and signaling pathways is described; followed by an overview of antiapoptotic cell line engineering strategies tested so far in CHO cells. Abstract : Chinese Hamster Ovary cell death, or apoptosis, poses a significant bioprocessing challenge, in particular for high cell density culture. Here, the main known mechanisms of apoptosis, triggered by external and internal signals, are explained. A critical summary of previous cell line engineering strategies used to inhibit apoptosis follows. This review, combined with CRISPR‐Cas9 based gene editing technologies, will expedite rational genetic engineering of biopharmaceutical production cell lines in the near future.